Comprehensive assessment of executive functioning following childhood severe traumatic brain injury: clinical utility of the child executive functions battery - Chevignard, Mathilde; Guerra, Amanda; Fliss, Rafika; Salah, Lucie; Pineau, Emmanuelle; Notteghem, Pauline; Roche, Jeanne; Huon, Caroline; Krasny Pacini, Agata; Le Gall, Didier; Fournet, Nathalie; Roulin, Jean-Luc; et al. (Frontiers in Psychology, 2023)
Objectives: To perform a detailed description of executive functioning following moderate-to-severe childhood traumatic brain injury (TBI), and to study demographic and severity factors influencing outcome.A convenience sample of children/adolescents aged 7-16 years, referred to a rehabilitation department after a TBI (n=43), was compared to normative data using a newly developed neuropsychological test battery (Childhood Executive Functions Battery -CEF-B) and BRIEF.Results: Performance in the TBI group was significantly impaired in most of the CEF-B subtests, with moderate to large effect sizes. Regarding everyday life, patients were significantly impaired in most BRIEF clinical scales, both in parent-and in teacher reports. Univariate correlations in the TBI group did not yield significant correlations between the CEF-B and socio-economic status, TBI severity, or age at injury.Executive functioning is severely altered following severe childhood TBI and is best assessed using a combination of developmentally appropriate neuropsychological tests and behavioral ratings to provide a comprehensive understanding of children's executive functions.